2014
DOI: 10.1002/erv.2320
|View full text |Cite
|
Sign up to set email alerts
|

Carers' Assessment, Skills and Information Sharing (CASIS) Trial: A Qualitative Study of the Experiential Perspective of Caregivers and Patients

Abstract: Caregiver interventions can be a useful tool that will improve the cost effectiveness of inpatient treatment by enhancing the well-being of caregivers and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 23 publications
(32 reference statements)
0
29
0
Order By: Relevance
“…In this study, one of the three components regarding self‐efficacy, disruptive behaviours (reduced hostility towards the patient), changed significantly , which may suggest a positive outcome for the patient (Macdonald et al . ). In one qualitative study, parents reported higher levels of self‐efficacy in coping with the illness after an intervention (Goodier et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, one of the three components regarding self‐efficacy, disruptive behaviours (reduced hostility towards the patient), changed significantly , which may suggest a positive outcome for the patient (Macdonald et al . ). In one qualitative study, parents reported higher levels of self‐efficacy in coping with the illness after an intervention (Goodier et al .…”
Section: Discussionmentioning
confidence: 97%
“…According to Macdonald et al . (), adolescents with eating disorders found meal support, increased responsibility and motivation to be helpful in the recovery process, whereas high family anxiety, detachment and/or a directive approach were unhelpful. In spite of the literature base regarding caregivers of people with eating disorders, the most beneficial factors affecting support remain unclear (Sepulveda et al .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, as in the sample in Hibbs, Rhind, et al (), the percentage of mothers who were the primary caregiver was notably higher than that of fathers. Previous studies on caregivers and ED patients have reported a larger number of mothers take on this role compared with fathers (Coomber & King, ; Graap et al, ; Jauregui‐Lobera, Ruiz‐Prieto, Bolanos‐Rios, & Garrido‐Casals, ; Macdonald et al, ; Martín et al, ). These results are in line with the current literature highlighting the predominance of female caregivers across mental disorders (Graap et al, ; Roick, Heider, Toumi, & Angermeyer, ; Souza et al, ; Stadnick, Chlebowski, & Brookman‐Frazee, ).…”
Section: Discussionmentioning
confidence: 98%
“…Partners need guidance on how to facilitate change constructively. Couple‐based treatments target potentially detrimental interpersonal dynamics and may improve outcomes, reduce relapse (Linville et al, ), and improve patient and partner quality of life (Macdonald et al, ). UNITE‐BED targets BED psychopathology, co‐occurring symptoms, and relationship functioning (Kirby, Runfola, Fischer, Baucom, & Bulik, ; Kirby, Runfola, Fischer, Baucom, & Bulik, ) by integrating core cognitive‐behavioral therapy (CBT) for BED principles (Fairburn, Cooper, & Shafran, ) with cognitive‐behavioral couple therapy interventions (CBCT; Epstein & Baucom, ).…”
Section: Introductionmentioning
confidence: 99%